The Influence of Educational Leadership in Successful Change Management in Education Office of Wolaita Zone - Lerra, Mulatu Dea (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to examine the influence of educational leadership in successful change management in Wolaita zone some selected woreda education offices. The target populations for this study were from Wolaita zone woreda educational offices. In Wolaita zone, there are 22 woredas/districts and 3 city administrations; among them three woreda education offices and one city administration education office were selected through simple random sampling and purposive sampling respectively. Therefore, total population of the study was 230; among them 63 expertise, 6 educational office leaders, 40 supervisors and 121 principals were selected by purposive sampling method. In order to collect data, questionnaires, was employed. This study was carried through descriptive survey design. The study revealed that the leader’s ability to influence the followers was poor and leaders not playing their leadership role appropriately. The finding also shows strong effect of leadership on successfully implementing change management process in the sampled study areas. Thus, one can recommend that leaders should motivate follower and change agent by being role mode land participatory. The leaders should develop and institutionalize appropriate strategy to implement change in the institutions.